STUDY OF ORE MINERALIZATION POTENTIAL IN METAMORPHIC ROCKS IN KAWATUNA AREA, PALU CITY, CENTRAL OF SULAWESI - Asrafil, Asrafil; Mukaddas, Abdul; Puspita, Riska; Assidiqi, Muhammad; Rugayya, Sitti (JGE (Jurnal Geofisika Eksplorasi), 2025)
The Kawatuna area has a complex geological structure and lithological condition of metamorphic rock, which is estimated to be a weak zone for hydrothermal solutions to rise and then accumulate as mineralization of veins in the metamorphic rock. Based on this, it makes this area interesting to research. This research aims to identify metal ore minerals and the mineralization characteristics of ores in the research area. The method used is a geological survey of the surface and laboratory analysis through ore microscopic as well as mineral chemistry tests. Based on the results of the research study, it was found that in metamorphic rocks in the Kawatuna area, sulfide metal ore minerals were found including argentite (Ag2S), pyrite (FeS2), chalcopyrite (CuFeS2), sphalerite (ZnS), galena (PbS), and covelite minerals (CuS), Native elements ore minerals include gold (Au), silver (Ag), electrum (Au, Ag), and Oxide ore minerals in the form of hematite (Fe2O3). The mineralization formed is controlled by structures that produce fractures in the rock, which then produces mineralization as the veins of metamorphic rocks. The ore mineralization in the research area occurs through a hypogene process (the formation of a formation zone from primary ore minerals) and a supergene process stage (the formation of a formation or enrichment zone from secondary ore minerals).